Knowledge, Attitude, and Preventive Practice Related to Onchocerciasis and Associated Factors among Resource-Limited Selamogo Woreda Residents, South West Ethiopia, 2021. (29th August 2022) - Gilano, Girma; Mulugeta shegaze,; Dubale, Amanuel
Abstract : Introduction . Ethiopians work very hard to control and eradicate the vector and the parasite of Onchocerciasis. However, some hard-to-reach areas are not adequately covered by interventions that have previously taken place in various endemic sites in the country. This study aimed to assess knowledge, attitude, and preventive practice of Onchocerciasis among Selamogo residents to enhance the expansion of interventions. Methods . We used a survey questionnaire to capture the data on 572 Selamago residents. We checked, cleaned, entered the data into EPI Info v.7, and analyzed it in STATA v.15. We fitted a binary logistic regression model to examine the associated factors. Variables significant at P < 0.20 were included in the model. We declared association at P < 0.05 . Results . Of the 578 residents we approached, 572 (99%) responded to the interview. We found 48.30% of poor knowledge, 90.90% of poor attitude, and 85.70% preventive practice related to Onchocerciasis. Factors like Amhara ethnicity (AOR = 2.35, 95% CI: 1.05, 5.27), Orthodox Christianity (AOR = 1.87, 95% CI: 1.12, 3.10), Muslims (AOR = 2.28, 95% CI: 1.05, 4.94), secondary school (AOR = 2.31, 95% CI: 1.50, 3.55), diploma (AOR = 10.34, 95% CI: 4.62, 23.16), and preventability of Onchocerciasis (AOR = 3.02, 95% CI: 1.39, 6.55) were associated with KAP. Other factors like medical treatability, admission history to the health facilities, sex, and the number of households were also associated. Conclusion . The KAP related to Onchocerciasis is very poor compared to the indicators and evidence in the country. An intervention that considers local resources like taking the experience of groups with good knowledge, attitude, and preventive practice led by educated plus positive attitude people regarding the preventability and treatability of Onchocerciasis might be mandatory to improve the status.